2013
DOI: 10.3329/jssmc.v5i2.20766
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Sensitivity Pattern of Uropathogenic Escherichia coli: Five Year Experience at a Tertiary Care Hospital in Dhaka

Abstract: Background: Urinary tract infections are among the most common bacterial infections caused by pathogens with a decreasing susceptibility to several classes of antimicrobials. Objective: The purpose of the present study was to see the trend of sensitivity pattern of Escherichia coli (E. coli) isolated from the urinary tract patients. Methodology: This retrospective study was conducted at Uttara Adhunik Medical College Hospital, Dhaka from 2008 to 2012 for a period of 5(five) years. All patients were within ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The highest percentage (44%) of study sample practiced midwifery at their house, and (37%) of them practiced midwifery at mother's house as shown in table (3). This finding is consistent with McCormick and Begum reported that the traditional birth attendants must go to the home of full term women, demonstrate and discuss the preparation of the delivery room with sufficient light in the delivery room and many births in developing countries occur in the home because of cultural preferences, economic reasons, poor quality services, or services that are difficult to access (11)(12) .…”
Section: Licensed Indigenous Midwives' Knowledge Prevention and Manag...supporting
confidence: 87%
See 1 more Smart Citation
“…The highest percentage (44%) of study sample practiced midwifery at their house, and (37%) of them practiced midwifery at mother's house as shown in table (3). This finding is consistent with McCormick and Begum reported that the traditional birth attendants must go to the home of full term women, demonstrate and discuss the preparation of the delivery room with sufficient light in the delivery room and many births in developing countries occur in the home because of cultural preferences, economic reasons, poor quality services, or services that are difficult to access (11)(12) .…”
Section: Licensed Indigenous Midwives' Knowledge Prevention and Manag...supporting
confidence: 87%
“…This table shows that (53%) of study sample have experiences in midwifery between (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 3) shows the highest percentage (96%) of study sample attended deliveries at the same area of midwives' house within their boundaries. The same table shows that (44%) of them conducted the deliveries at their houses while 37% of them conducted delivery at mother's house.…”
Section: Table 1 Distribution Of Demographic Characteristics Of the S...mentioning
confidence: 96%
“…Gradual decrease of susceptibility pattern of mecillinam was found. 58 In our study, Klebsiella was 100% sensitive to flucloxacillin, colistin, vancomycin, tigecycline, linezolid and 100% resistant to nalidixic acid. Begum et.al.…”
Section: Discussionmentioning
confidence: 91%
“…analyzed 16,666 urine samples to see the trend of sensitivity pattern of uropathogenic Escherichia coli at Uttara Adhunik Medical College Hospital, in Dhaka. 58 They found that A total number of 16, 666 reports of urine samples were collected from the microbiology laboratory data base of which 3,000(18%) reports showed presence of E. coli. E. coli were mostly susceptible to meropenem from the year 2008 to 2012 (100%) except 2010 (98.58%) followed by amikacin (81.20%-100%) and imipenem (78.66%-100%).…”
Section: Discussionmentioning
confidence: 99%